GLOBAL TRENDS AND PROSPECTS FOR THE DEVELOPMENT OF BUSINESS TOURISM IN MODERN CONDITIONS (Development Service Industry Management, 2025)
The article explores the global trends and prospects of business tourism development, primarily based on an analysis of annual reports and forecasts published by the Global Business Travel Association. It highlights the key countries dominating the MICE (Meetings, Incentives, Conferences, and Exhibitions) industry, which have been at the forefront of business tourism growth, and presents the prospects for its expansion under contemporary conditions. The paper also gives special attention to the unique challenges faced by business tourism in Ukraine, particularly against the backdrop of ongoing security threats, economic instability, and limitations in infrastructure development.The study examines the complex interdependence between business tourism and the broader global digitalization systems. This includes an analysis of various economic, technological, informational, sociocultural, and regulatory factors that influence business tourism's evolution. The article emphasizes the importance of state support, which could be realized through the establishment of national convention bureaus, as well as the need to promote public-private partnerships to foster the development of the sector. By doing so, Ukraine could improve its competitive positioning in the global market of business tourism.Another critical point discussed is the integration of sustainable environmental practices into the business tourism industry. The article advocates for the adoption of digital technologies to streamline and enhance the efficiency of organizing business events. It argues that the implementation of such technologies could improve the overall business tourism experience, offering more personalized and effective solutions for organizing events, and making them more environmentally responsible. Furthermore, the adoption of these innovations could strengthen Ukraine’s competitiveness in the global business tourism market, attracting more international business visitors and enhancing the country’s reputation as a modern and innovative destination for business events.In conclusion, the article underscores that global trends in business tourism are shifting towards greater integration with digital technologies, sustainability, and collaboration between public and private sectors. By addressing its internal challenges and leveraging these global trends, Ukraine has the potential to enhance its role in the international business tourism industry.
Keywords: business tourism; MICE industry; business travel; global business expenditures; business event infrastructure; hybrid event formats; global digitalization systems; environmental sustainability